Deep vein thrombosis in bilateral lower extremities after hip fracture: a retrospective study of 463 patients - Zhang BF (Dove Medical Press, 2018)
Bin-Fei Zhang,* Xing Wei,* Hai Huang, Peng-Fei Wang, Ping Liu, Shuang-Wei Qu, Jia-Hao Li, Hu Wang, Yu-Xuan Cong, Yan Zhuang, Kun Zhang Department of Orthopedic Trauma, Hong-Hui Hospital, Xi’an Jiaotong University College of Medicine, Beilin District, Xi’an, Shaanxi, China *These authors contributed equally to this work Objective: To investigate the incidences of deep vein thrombosis (DVT) before and after operation in inpatients with hip fractures in both lower extremities.Patients and methods: We collected the clinical data of 463 patients with lower extremities fractures who presented at Xi’an Honghui Hospital between July 1, 2014, and October 31, 2016 and met all the inclusion criteria. Doppler ultrasonography was used to diagnose DVT. The patients were examined preoperatively and postoperatively and divided into the thrombosis and non-thrombosis group according to the ultrasonographic findings. We divided the DVT cases into central, peripheral, and mixed thromboses.Results: The incidence of preoperative DVT was 34.98%, and the prevalence of DVT on the uninjured side was 13.60%. This composition ratio increased to 57.23% postoperatively, and the prevalence of DVT on the uninjured side was 25.05%. Age (odds ratio [OR], 1.03; 95% CI: 1.01–1.04; P=0.002), venous thrombosis at admission (OR, 4.05; 95% CI, 2.30–7.13; P=0.000), and the days between the fracture and the operation (OR, 1.10; 95% CI, 1.02–1.20; P=0.020) were the independent risk factors of preoperative DVT. Coronary heart disease (OR, 1.85; 95% CI: 1.18–2.89; P=0.007), venous thrombosis at admission (OR, 22.35; 95% CI: 6.78–73.60; P=0.000), days between fracture and operation (OR, 1.06; 95% CI: 1.01–1.11; P=0.021), and blood loss (OR, 1.002; 95% CI: 1.000–1.003; P=0.014) were independent risk factors of postoperative DVT.Conclusion: The actual incidence of DVT after hip fracture may be underestimated. The incidences of preoperative and postoperative DVTs and the incidence of DVT on the uninjured limb were high. Keywords: deep vein thrombosis, ultrasonography, hip fracture, anticoagulation, low-molecular-weight heparin